2016
DOI: 10.4149/neo_2016_414
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac tamponade – unusual clinical manifestation of undiagnosed malignant neoplasm

Abstract: Cardiac tamponade may be the first or predominant symptom of some pathologies but its etiology is not uncommonly unknown on admission to hospital. The purpose of this study was to evaluate the predominant causes of cardiac tamponade in previously healthy patients treated emergently in a single cardiac surgical center. The study involved 81 patients with the mean age of 58.1±16.0 years who underwent emergent subxyphoid pericardiotomy due to cardiac tamponade. Pericardial effusion was analyzed macro- and microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Other causes of postoperative hemopericardium are as follows. First, the most common malignancies with cardiac metastases include melanoma and primary mediastinal malignancies [ 12 ], which did not include the tumors in our cases. Additionally, metastatic tumors of the heart must involve the pericardium to give rise to hemopericardium.…”
Section: Discussionmentioning
confidence: 99%
“…Other causes of postoperative hemopericardium are as follows. First, the most common malignancies with cardiac metastases include melanoma and primary mediastinal malignancies [ 12 ], which did not include the tumors in our cases. Additionally, metastatic tumors of the heart must involve the pericardium to give rise to hemopericardium.…”
Section: Discussionmentioning
confidence: 99%
“…Only eight of those 47 patients had positive pericardial fluid cytology. 7 Kim et al 8 studied 98 patients with known active malignancy who underwent pericardiocentesis for tamponade or imminent tamponade and reported that 75 of 98 samples (77%) had positive cytology. All 23 negative samples were exudative, and there were no alternative explanations for the effusions, so they were considered malignant.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that as many as 20% of pericardial effusions without an obvious cause after routine evaluation constitute the initial manifestation of a cancer [2]. Indeed, Perek B et al concluded in their study of 81 previously healthy patients, which cardiac tamponade was the main symptom of cancer, especially of the lungs [3].…”
Section: Discussionmentioning
confidence: 99%